Hepatoprotective effects of allyl isothiocyanate against carbon tetrachloride-induced hepatotoxicity in rat. (25th July 2016) - Ahn, Meejung; Kim, Jeongtae; Bang, Hyojin; Moon, Jihwan; Kim, Gi Ok; Shin, Taekyun
Abstract: We evaluated the hepatoprotective activity of allyl isothiocyanate (AITC) against carbon tetrachloride (CCl4 )-induced liver injury in rats. Sprague Dawley rats were orally administered AITC at doses of 5 (AITC 5) and 50 (AITC 50) mg/kg body weight once daily for 3 days, with or without intraperitoneal injection of CCl4 . Serum chemistry was assessed for changes in alanine aminotransferase (ALT) and aspartate aminotransferase (AST). The enzyme activities of superoxide dismutase (SOD), catalase (CAT), and malondialdehyde (MDA) were examined in liver tissues, while pro-inflammatory cytokines including tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β) mRNA expression were analyzed using real-time polymerase chain reaction. And heme oxygenase-1 (HO-1) and ionized calcium binding protein-1 (Iba-1) immunoreactivities were evaluated by Western blot analysis and immunohistochemistry, respectively. In serum chemistry, the oral administration of AITC itself did not affect the serum levels of ALT or AST, furthermore pretreatment with AITC 5 and AITC 50 significantly reduced the ALT and AST activity levels that were elevated in CCl4 -intoxicated rats. In addition, AITC significantly suppressed the reduction of SOD and CAT, and the elevation of MDA, TNF-α mRNA expression, on the other hands, induced the expression of HO-1 compared with those of the vehicle-treated CCl4 group. The histopathological evaluation and Iba-1 immunoreactivity also supported the hepatoprotective effects of AITC against CCl4 -induced liver injury. These results suggest that AITC ameliorates oxidative liver injury, possibly through reducing lipid peroxidation, enhancing antioxidant enzymes, and suppressing Kupffer cells and macrophages. Highlights: AITC ameliorated the hepatotoxicity after CCl4 challenge. AITC suppressed the activation of Kupffer cells and macrophages. HO-1 enzyme was increased after AITC treatment. AITC has potential to protect against oxidative stress-induced liver injury in a rat model.